Analyzing the Correlation Between Social Media Influencers and Customers’ Intention to Buy in the Luxury Market - Agrawal, Charul; Duggal, Taranjeet; Shukla, Vishal; Dohroo, Mitali (Indian Journal of Marketing, 2023)
Purpose : The present study analyzed the impact of expertise, authenticity, and advertisement disclosure by social media influencers (SMI) on the purchased intention of luxury goods with the moderated role of gender. The growth of social media platforms has accentuated the need to understand the implications of SMIs. Methodology : The data for the study were collected via Google Forms from 400 respondents. The variables, namely expertise, authenticity, and advertisement disclosure by SMIs, were chosen after studying extensive literature. All these variables were analyzed, keeping gender as a moderating variable; whereas, purchase intention was the dependent variable. The data collected were analyzed using AMOS. Findings : The study revealed that all three independent variables, namely expertise, authenticity, and advertisement disclosure, were positively related to purchase intention. However, no significant relationship was observed when gender was studied concerning advertisement disclosure. Practical Implications : The study would be helpful to luxury market companies where they can evaluate the utility of SMIs when it comes to luxury shopping. It also provided insights into what aspect of SMIs was paramount for luxury consumers. Originality : The previous studies have focused on luxury shopping and its antecedents for purchase; this study specifically concentrated on three crucial variables directly associated with SMIs and how they could influence the purchase decisions.